Pembentukan dan Makna Deverbal Compound Nouns pada Kata Majemuk Bahasa Jepang: Studi Kasus pada 15 Kata Majemuk: The Formation and Meaning of Deverbal Compound Nouns in Japanese Compound Words: A Case Study of 15 Compound Words - Ni Putu Meta Maharani; Yasinta Tawo (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study examined the formation process and semantic meanings of deverbal compound nouns in Japanese. Deverbal compound nouns were defined as compound words formed from verbs that had undergone nominalization, primarily through the renyoukei form. The aim of this study was to describe the morphological processes, semantic characteristics, and the relationship between the original verbs and the newly formed meanings in fifteen Japanese compound nouns. A qualitative descriptive method was employed, and the data were collected from the Kotobank.jp dictionary. The analysis was conducted using the immediate constituent analysis method to identify morphemic structures, as well as the theories of Lexical Conceptual Structure (LCS) and Qualia Structure to explain the semantic relations among the constituent elements. The results show three main formation patterns of deverbal compound nouns, namely N + V (連用形)˜, V (連用形) + V ((連用形), and VN constructions that can function as predicates through the suru construction. Semantically, three dominant tendencies are identified, namely idiomatic meaning, process meaning, and resultative meaning. These findings indicate that the formation of deverbal compound nouns involves not only morphological processes but also mechanisms of semantic conceptualization in Japanese.